Intelligent Virtual Agents 12th International Conference, IVA 2012, Santa Cruz, CA, USA, September, 12-14, 2012. Proceedings - Nakano, Yukiko; Neff, Michael; Paiva, Ana.; Walker, Marilyn; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 12th International Conference on Intelligent Virtual Agents, IVA 2012, held in Santa Cruz, CA, USA, in September 2012. The 17 revised full papers presented together with 31 short papers and 18 poster papers were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on IVAs on learning environments; emotion and personality; evaluation and empirical studies; multimodal perception and expression; narrative and interactive applications; social interaction; authoring and tools; conceptual frameworks.
IVAs on learning environments -- emotion and personality -- evaluation and empirical studies -- multimodal perception and expression -- narrative and interactive applications -- social interaction -- authoring and tools -- conceptual frameworks.
Keywords: Computer science; Computer Communication Networks; Artificial intelligence; Computer simulation; Computer vision; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).; Computer Communication Networks; Image Processing and Computer Vision; User Interfaces and Human Computer Interaction; Simulation and Modeling